1988
DOI: 10.1073/pnas.85.16.6077
|View full text |Cite
|
Sign up to set email alerts
|

CD3-associated heterodimeric polypeptides on suppressor hybridomas define biologically active inhibitory cells.

Abstract: We have investigated the relationship between CD3 expression and the suppressor T-cell function. We have isolated stable clonal cell lines of the F12.23 suppressor T-cell hybridoma that are either CD3+ or CD3-. These lines were subjected to functional assays including inhibition of in vivo hapten-specific delayed-type hypersensitivity responses, in vitro hapten-specific interleukin 2 responses, as well as haptenspecific cytotoxic T-lymphocyte assays. In all assays, the functional suppressor phenotype absolutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…(11). This observation has been confirmed in other suppressor T-cell systems (12,24,25). Recently, a series of Ts hybridomas was prepared by fusion with the TcR a-73-BW1100 thymoma; all Ts, hybridomas from this fusion express Ts donor-derived TcR a/,8 complexes (10).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…(11). This observation has been confirmed in other suppressor T-cell systems (12,24,25). Recently, a series of Ts hybridomas was prepared by fusion with the TcR a-73-BW1100 thymoma; all Ts, hybridomas from this fusion express Ts donor-derived TcR a/,8 complexes (10).…”
Section: Discussionsupporting
confidence: 72%
“…Subsequent analyses of Ts hybridomas indicated that Ts do express TcR a-chain mRNA derived from the Ts donor (3,4) and that some express the CD3-TcR a/(3 complex on their surface (5)(6)(7)(8)(9)(10)(11). Selection of Ts hybridomas for expression of surface CD3 resulted in an increase in antigen binding (11) and suppressive bioactivity (11,12). Molecular analysis of three 4-hydroxy-3-nitrophenyl acetyl (NP)-specific suppressor effector (Ts3) hybridomas indicated that each expressed a donor-derived TcR a chain and a TcR (3 chain derived from the BW5147 fusion partner (4).…”
mentioning
confidence: 99%
“…A possible resolution of the controversy surrounding TCR in regulatory T cells may come from the recent results of Weiner and colleagues (24). They found that a very small population (1-3%) of T3' cells in their cloned suppressorinducer T-cell hybridoma, F12, was responsible for all of the production of antigen-specific factor by this cell.…”
Section: Discussionmentioning
confidence: 99%
“…Our efforts to understand suppressor T cells and their factor(s) began several years ago and have continued to some extent in several systems (22)(23)(24)(25). Recent interest in this area once again is obvious.…”
Section: Discussionmentioning
confidence: 99%